GRAPHO-ANALYTICAL MODELING OF PROCESSES OF INTERACTION OF ELEMENTARY COMPONENTS OF A MANAGEMENT PAIR (International Journal of Innovative Technologies in Economy, 2018)
In order to analyze and justify the choice of the recommended modes of interaction of people in organizational entities, the article covers the main possibilities of increasing the effectiveness of human interaction on the basis of interpreting a typical management pair in the form of two elementary components that can interact in the "subject-object", "subject-subject”, “object-subject” and “object-object” modes, taking into account the fact that each component is characterized by a certain level of subjectivity. At the same time, the authors take into account the fact that during the life of a person and its life cycle in an organizational formation the level of subjectivity of any person varies within the boundary of the linear continuum object - subject, and its subjectity in organizational formation is defined by no means other, as the current state of the ratio of the number of formal and informal influences of the individual as a subject to other members of the organization to the number of the same effects on it as an object from other members of the organization. Due to the fact that the life cycles of the elementary components are characterized by the presence of each of the periods of increase in subjectivity with the achievement of each peak value and the subsequent gradual loss after release or retirement, it is demonstrated that the joint and equally effective activity of the components is possible only provided that they maintain the subject-subject mode of interaction, which corresponds to the dialogue of the two parties, rather than management of or management by one side of the other. Using the superposition of graph- analytic dependencies of Dunig-Kruger and changes in subjectivity throughout life, it is proved that the basic condition for the implementation of such a managerial dialogue is the awareness of both components of the managerial pair of the fact that the concept of the subject loses meaning without the existence of the object, and therefore maintaining the process of dialogue-cooperation is possible only under the condition of equality and freedom of the participants and the inter-orientation of each of the partners as the subject, the tool for establishing partnerships is management on the basis of the dialogue communication process with the mutual recognition of each of the participants in their freedom, equality and value - subjectivity. It has been established that the priority factors determining the results of the operation of a typical management pair are not the structure and the relationship between its constituent elements, but the intellectual, moral and psychological characteristics of these elements and the awareness of the latter as partners that jointly solve the problem with the achievement of mutually established and harmonized goals.